Evaluation and improvement of workplace vertical violence of nursing interns based on the Importance-Performance Analysis method - Xu, Weifang; Feng, Lili; Huang, Haohao; Liu, Siqi; Ye, Mao; Tang, Fuqin; Chuang, Yen-Ching; Cai, Fuman (Frontiers in Medicine, 2023)
Purpose To analyze the key factors related to workplace vertical violence among nursing interns in China and to propose strategies to improve the nursing practice environment. Methods A cross-sectional study was conducted using the Importance-Performance Analysis (IPA) method to analyze the key factors and significance of workplace vertical violence for nursing interns. The data were obtained by administering a workplace vertical violence survey, designed specifically for this study, to 120 nursing interns at a tertiary general hospital in Zhejiang Province, China. Results The results demonstrated that the variables “I was ordered to do something beyond my ability and lacked guidance (C3),” “Errors in work have been repeatedly emphasized, spread, or exaggerated (C8),” “I was unjustly criticized (C9),” “I was withheld or blocked information purposefully (C1),” and “I was belittled at work (C2)” were the most crucial variables for determining the presence of workplace vertical violence of nursing interns. Moreover, they are priority improvement variables. Conclusion Managers must prioritize the use of relevant resources during internships to minimize false reinforcement and unfair criticism. Efforts should focus on improving information sharing, emphasizing the role of nursing interns in clinical work, providing better guidance when arranging for nursing interns to do work that exceeds their capacity, reducing workplace vertical violence, and improving nursing intern practice environments.